Comparison of gabapentin versus topiramate on clinically affected dogs with Chiari‐like malformation and syringomyelia. (19th September 2015) - Plessas, I. N.; Volk, H. A.; Rusbridge, C.; Vanhaesebrouck, A. E.; Jeffery, N. D.
Abstract : To date there is no evidence‐based data for efficacious treatment of neuropathic pain in dogs with Chiari‐like malformation (CM) and syringomyelia (SM). The objective of this prospective cross‐over study was to compare the effect of gabapentin versus topiramate, as an add‐on treatment to carprofen, on quality of life (QoL) of dogs experiencing signs of neuropathic pain due to CM/SM. A visual analogue scale (VAS) was used to assess the QoL: (1) on day 0; (2) after 1 week of carprofen only; (3) after 2 weeks on carprofen and gabapentin; and (4) after 2 weeks on carprofen and topiramate. No significant difference was observed between VAS after gabapentin or topiramate (P=0.91). However, an improvement in QoL was observed when gabapentin was compared with baseline (P=0.009), but not for topiramate. In conclusion, the addition of gabapentin was more effective in improving QoL than carprofen alone, but the study failed to identify that gabapentin was more efficacious than topiramate. Perhaps the more favourable side effect profile of the former makes it more suitable for the treatment of neuropathic pain associated with CM/SM but further placebo‐controlled trials are required to assess the efficacy of these drugs.